The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 18th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2015
DOI: 10.1145/2675133.2675216
|View full text |Cite
|
Sign up to set email alerts
|

Making "Safe"

Abstract: The use of online games and virtual worlds is becoming increasingly prominent, particularly in children and young adults. Parents have concerns about risks their children might encounter in these online spaces. Parents dynamically manage the boundaries between safe and unsafe spaces online through both explicit and implicit means. In this work, we use empirical data gathered from a digital ethnography of a Minecraft server, Autcraft, to explore how parents of children with autism continually create a "safe" vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…These results provide further evidence that informational and emotional support are types of exchanges that are commonly sought and provided by individuals who are coping with chronic diseases. Although not health-related, Ringland et al [63], explored how parents constructed a safe online space for children with autism in a game called Autcraft. This positive and supportive gaming environment provides a space for children with autism to play games and interact with lower risk of discrimination or bullying, which provides insight into the larger questions of what online safety might look like for vulnerable populations, such as those with dementia.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…These results provide further evidence that informational and emotional support are types of exchanges that are commonly sought and provided by individuals who are coping with chronic diseases. Although not health-related, Ringland et al [63], explored how parents constructed a safe online space for children with autism in a game called Autcraft. This positive and supportive gaming environment provides a space for children with autism to play games and interact with lower risk of discrimination or bullying, which provides insight into the larger questions of what online safety might look like for vulnerable populations, such as those with dementia.…”
Section: Related Workmentioning
confidence: 99%
“…This positive and supportive gaming environment provides a space for children with autism to play games and interact with lower risk of discrimination or bullying, which provides insight into the larger questions of what online safety might look like for vulnerable populations, such as those with dementia. The design of Autcraft allows parents to set up rules and guidelines to allow their children's virtual gaming experience to be safe based on their unique personal conception of what safety looks like for their child [63]. Ringland et al found that there were distinct conceptualizations of what a safe space meant for different parents; however, there were commonalities in that parents perceived risks to their children's safety across emotional, physical, and social domains.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…As for emotional problems, VR can also be effective [56,74,75]. VR is also potentially useful in working the access to the job market [12,76,77].…”
Section: Virtual Reality (Vr) and Asd Postsecondary Studentsmentioning
confidence: 99%